Karakteristik Komposit Biotermoplastik Dari Pati Termoplastik/Glukomanan Termoplastik/Poliasam Laktat Dalam Variasi Jenis dan Konsentrasi Compatibilizer - Saragih, Ruth Natasya Octaviani; Harsojuwono, Bambang Admadi; Suhendra, Lutfi; Amna , Amna; Suhartini, Sri (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Biotermoplastic is a one of the innovation to improve the physical and mechanical properties of bioplastics. This study aims to determine the effect of the type and concentration of compatibilizer on the characteristics of biothermoplastic composites and to determine the type and concentration of the right compatibilizer to produce the best characteristics of biothermoplastic composites of thermoplastic starch/thermoplastic glucomannan/polylactic acid (TPS/TPG/PLA). This research utilizes a Completely Randomized Design (CRD) with 6 treatments, namely J1KI (maleic acid anhydride 5%), J1K2 (maleic acid anhydride 7,5%), J1K2 (maleic acid anhydride 10%), J2K1 (stearic acid 5%), J2K2 (stearic acid 7,5%), and J2K3 (stearic acid 10%), with 3 replications. The variables observed in this study were tensile strength, elongation at break, elasticity, swelling, density, melting point and biodegradation time. The data were analyzed by analysis of variance (ANOVA) and further tested using the Honestly Significant Difference (HSD) test. The results showed that the type and concentration of compatibilizer had a very significant effect on the values ​​of tensile strength, elongation at break, elasticity, swelling, density, melting point and biodegradation time. The best characteristics of biothermoplastic composites of thermoplastic starch/thermoplastic glucomannan/polylactic acid were obtained by using 10% anhydrous maleic acid compatibilizer with a tensile strength value of 30.43 MPa, an elongation at break of 0.90%, elasticity of 3.38 GPa, swelling of 0.51%, density of 1.52 g/cm3, melting point of 149.77oC and biodegradation time of 17.667 days.